1999
DOI: 10.1021/jp983315y
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Photoinduced Electron Transfer at C60-EDTA Langmuir−Blodgett Film Modified ITO Electrode

Abstract: The monolayer and multilayer films of an amphiphilic C 60 -EDTA (C 60 EA) and its tetramethyl ester (C 60 EM) were fabricated on semiconducting transparent ITO electrodes by the Langmuir-Blodgett (LB) technique. The photoelectric response of the modified electrodes was measured under various conditions to explore possible mechanisms of the electron transfer in this light harvesting and conversion system. The action spectrum of photocurrent implicates the excited C 60 EA or C 60 EM as the photoactive species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
1
31
2
Order By: Relevance
“…The photocurrents observed in the present study are two to three orders of magnitude greater than the recently reported photoelectrochemical cells using functionalized fullerenes [22,24] and an order of magnitude greater than the photovoltaic cell designed with a C 60 ± oligophenylenevinylene. [39] Note that the photocurrent measurements in the present study were done with a yellow corning filter (425 nm cutoff), which only allow for long wavelength excitations.…”
Section: Resultscontrasting
confidence: 68%
“…The photocurrents observed in the present study are two to three orders of magnitude greater than the recently reported photoelectrochemical cells using functionalized fullerenes [22,24] and an order of magnitude greater than the photovoltaic cell designed with a C 60 ± oligophenylenevinylene. [39] Note that the photocurrent measurements in the present study were done with a yellow corning filter (425 nm cutoff), which only allow for long wavelength excitations.…”
Section: Resultscontrasting
confidence: 68%
“…Previous efforts to cast fullerene films using solvent evaporation, [1,2] Langmuir±Blodgett films, [3,4] self-assembly of monolayers, [5,6] or layer-by-layer assembly, [7] have produced polymorphous films. However, a high degree of molecular order has been achieved with the films formed on a highly oriented pyrolytic graphite (HOPG).…”
mentioning
confidence: 99%
“…Recently, C 60 -derived self-assembled monolayers (SAMs) have been reported to exhibit a wide range of interesting properties such as charge transport, photo-conductivity, superconductivity, and biological activities [1][2][3][4][5][6][7]. Because of its electron-affinitive nature, it is possible to induce very efficient electron transfer from various photoexcited electron donors to C 60 [4]. C 60 s covalently bounded to conjugated molecules have been reported to form a long-lived charge-separated state via photoinduced electron transfer [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%